Feed Formulation from Locally Available Cheap Sources and its Effect on the Growth of Tilapia (Oreochromis Mossambicus) - Noureen, Sadaf; Narejo, Naeem Tariq; Tariq, Nabeela; Naeem , Muhammad; Iqbal, Rehana (International Journal of Psychosocial Rehabilitation, 2020)
This study work was completed to check the effectiveness of local feed for fish growth. For this purpose, easily available feed ingredients were collected from the local market. 100 fingerlings of Oreochromis mossambicus were collected from Bahawalpur fish hatchery and these samples were kept under feeding trial in the fish laboratory of Institute of Pure and Applied Biology (Zoology Division) at Bahaudin Zakariya University, Multan. This study was prolonged for 60 days. Three feeds were prepared and fed to the 3 experimental fish groups. 15 fingerlings were analyzed for growth parameters and fish body composition. This study presented that fish growth can be increased by replacing commercial expensive feed by local easily available food sources. Non-significant (p > 0.05) value of feed conversion ratio was obtained and feed efficiency ratio was also documented as non-significant (p > 0.05). Highly significant (p < 0.001) value of protein efficiency ratio and specific growth rate was achieved. Different content values of water, dry weight, ash, organic matter, fat and protein were analysed.